Structural characteristics of mangrove forests in Brazilian estuaries: A comparative study - Camargo Maia,Rafaela (Universidad de Valparaíso. Facultad de Ciencias del Mar, 2012)
The aim of this study was the characterization of mangrove forests in 9 estuaries in the state of Ceará, northeastern Brazil, with the purpose of comparing them and providing subsidies for their conservation. We used the method of multiple squares, having 3 transects of 5 quadrats at each site. We obtained values for the diameter and basal area of the individuals, dominance, trunk density and relative frequency per species, as well as variables for the analysis of sediment. The results obtained regarding structural parameters showed differences among the sampled forests, where the highest density levels were found in the Acaraú, Ceará and Guriú rivers. The Guriú River also presented the smallest values for height, Diameter at Breast Height (DBH) and basal area. The grouping analysis indicates 3 groups of forests: 1) Cocó and Ceará; 2) Acaraú, Jaguaribe and Pacoti, and 3) Aracatimirim and Guriú. The mangrove forests in Curú and Barra Grande were not grouped. The Principal Component Analysis (PCA) indicated that the sediments collected in the estuaries present a distinct texture composition. The differences between the areas must be taken into consideration when proposing management, as each mangrove demands different strategies for its maintenance.